Extensive Listening in the Eyes of Pre-Service English Teachers - Kukuh Dwi Pamuji (DIDAKTIKA, 2025)
The interest in using extensive listening (EL) in ELT pedagogy is emerging. This study scrutinized the views of pre-service English teachers on the concepts of EL and their views on the implementation of EL in the ELT classroom. Using the qualitative descriptive design, this study collected the data from two pre-service English teachers who attended the Extensive Listening course for four months with a total of 14 meetings. They participated in learning the concepts of EL, doing EL inside the class, and practicing EL conveniently outside the class. The data were collected using open-ended questionnaires at the end of the semester. The data collected were then analyzed using thematic analysis. The findings of this study revealed that the pre-service English teachers routinely practiced EL by listening to English materials on various topics. EL was reported to help them enhance their L2 aural vocabulary knowledge and hone their other language skills. Having an adequate understanding of the EL concepts, both the pre-service English teachers agreed on the inclusion of EL in the ELT curriculum at the school level. They also provided explanations of the possible challenges of using EL in class and how to overcome it. This study can be a source of inspiration for English teachers who are interested in implementing EL in the ELT classroom.